Improved quality of life after conservative treatment of obesity - A retrospective observational study - Pettersen, Charlotte (UiT Norges arktiske universitet, 2021)
Introduction: Obesity is a global and national health challenge. In Norway 23.0% of adults are obese. The clinical treatment for obesity is weight loss, either surgical or conservative. However, there is limited research on health-related quality of life (HRQoL) and conservative treatment of obesity. The primary aim of this study is to investigate changes in HRQoL from baseline to post-treatment for obesity. Secondary aims are what factors of HRQoL weight change potentially affects, and if a significant weight loss improves HRQoL in individuals with obesity. Material and method: 50 patients that had finished a three-year conservative treatment of obesity at Skibotn Health and Rehabilitation were included in this study. The participants were divided into a weight-loss group (WL group) and a weight-gain group (WG group). To measure HRQoL, 36-Item Short Form Health Survey (SF-36) was used. The SF-36 measures HRQoL across eight domains. Data at baseline and post-treatment was analyzed. Results: Post-treatment the whole group had a 12.5% improvement in bodily pain, and the WG group had a 6.0% improvement in mental health, and a 12.5% improvement in social functioning. The WL group had no significant changes post-treatment, but had several at year two, including improved physical functioning, physical role functioning, vitality, and bodily pain. The WG group had a significantly reduced mental health at year two, with a median change of -4.0%, but a significantly increased mental health at the end of the treatment, with a median change of 6.0% from baseline. Conclusion: There were some improvements in HRQoL from baseline to post-treatment. The aspects of HRQoL that changed post-treatment were bodily pain, emotional wellbeing, and social functioning. All participants had a 12.5% improvement in bodily pain, and the WG group had a 6.0% improvement in mental health and a 12.5% improvement in social functioning. One can therefore state that weight gain showed positive changes within the mental health aspect of HRQoL.